ANALISIS INTEGRASI GAMBAR TEKNIS MULTI-BIDANG SERTA OPTIMALISASI PENGGUNAAN SOFTWARE CAD PADA PROYEK JALAN TOL - Edison Hatoguan Manurung; Ichwan Wahyudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Design–construction conflicts are one of the major challenges in toll road construction projects, which often lead to delays, cost overruns, and reduced construction quality. These conflicts are commonly caused by inconsistencies in technical drawings, insufficient multidisciplinary coordination, and limitations in technical communication between planning and implementation teams. This study aims to analyze the integration of multidisciplinary technical drawings and the optimization of Computer Aided Design (CAD) usage as an effort to prevent construction design conflicts in toll road projects. The research method employs a structured literature review and descriptive analysis of planning and construction practices commonly applied in toll road projects in Indonesia. The results indicate that effective integration of technical drawings, supported by standardized CAD practices such as layer management, drawing coordination, and systematic design revisions, can significantly improve coordination effectiveness and reduce the potential for design conflicts during construction. The study concludes that CAD-based multidisciplinary drawing integration represents a practical, realistic, and applicable approach for large-scale infrastructure projects, particularly in contexts where full implementation of Building Information Modeling (BIM) has not yet been fully adopted.